Asset confiscation in Europe – past, present, and future challenges. Issue 2 (1st April 2019) - Boucht, Johan
Abstract : Purpose: The purpose of this paper is to paint a general picture of the asset confiscation regimes used in Europe and to outline potential challenges, practical and related to issues of principle, associated with the current development with regard to the confiscation of the proceeds of crime and criminals' proceeds. Design/methodology/approach: The paper endeavours to analyse the various steps of the confiscation process, and the various approaches to the confiscation of proceeds of crime and criminals' proceeds from a holistic perspective. The findings of the paper are based on a literature review along with a legal analysis of the existent legal frameworks. Findings: It is suggested that the efficiency of asset confiscation should be looked at from a holistic perspective involving the entire confiscation process, and not only focus on the confiscation powers awarded to the courts. Challenges relating to efficiency exist along the entire process, from the stage of financial investigations to the enforcement stage. Some of the methods used for confiscating criminal proceeds are becoming very far-reaching and raise concerns related to basic principles of criminal law and criminal procedural law. Research limitations/implications: This paper is not based on empirical research relating to, for example, the efficiency of confiscation. More empirical research would, however, be welcome in this field. Practical implications: The paper suggests that the efficiency of asset confiscation is contingent on the entire confiscation chain functioning efficiently. Before new and more repressive measures are introduced, the existing legal framework should be fully deployed and the concrete needs for new tools clearly delineated. Originality/value: The paper analyses confiscation with a view to the entire chain rather than merely looking at a particular confiscation scheme.